Dynamic Performance Analysis of Permanent Magnet Hybrid Stepper Motor by Transfer Function Model for Different Design Topologies - E.V.C Sekhara Rao; P.V.N Prasad (International Journal of Electrical and Computer Engineering (IJECE), 2012)
This paper discuss about dynamic performance analysis of permanent magnet hybrid stepper motor during single stepping by transfer function model for eight topologies using PDE toolbox of Matlab, for different current densities for two types of core materials.. These results suggest modifications for better performance of the PMH stepper motor for better dynamic response during single stepping.DOI:http://dx.doi.org/10.11591/ijece.v2i2.195